Reforming home energy consumption behavior based on mining techniques: a collaborative home appliances approach - Idrees, Amira M.; Shaaban, Essam M. (Kuwait Journal of Science, 2020)
Energy Consumption has become one of the strategic objectives all over the world which is not only the enterprises obligation but it should also be all citizens’ obligation. Focusing on individuals’ energy consumption, a vital approach for saving energy is a collaboration strategy which aims at sharing the home appliances for best usage. In this research, an approach is proposed for recommending the collaboration plan for adjacent houses in different perspectives, they are sharing appliances and minimizing the consumption rate. The research adopts the mining techniques in order to explore the required associations targeting to build the road map for appliances consumption. Representing the proposed approach is performed through a formal representation to the contributed stakeholders and their relations, representing the relations and the required associations in a semantic network represents ion, and each stage is discussed in details. The research applied the experiment on two of the benchmark datasets which references are mentioned, all stages are applied and associations are explored with confidence above 90% and the results confirmed the applicability of the proposed approach